Clinicopathological investigation of lymph node metastasis predictors in superficial esophageal squamous cell carcinoma with a focus on evaluation of lympho-vascular invasion. (1st October 2013) - Mitobe, Jimi; Ikegami, Masahiro; Urashima, Mitsuyoshi; Takahashi, Hiroyuki; Goda, Kenichi; Tajiri, Hisao
Abstract: Objective. Reliable indicators of the risk of lymph node metastasis (LNM) in superficial esophageal squamous cell carcinoma (sESCC: intramucosal and submucosal invasive carcinoma) may contribute to assist optimal clinical decision-making for treating sESCC. In esophageal cancer, there is a possibility of metastasis, even in sESCC, and careful evaluation is needed when making a pathological diagnosis. In this study, we objectively evaluated predictive factors of LNM. Materials and methods. A total of 110 consecutive sESCC cases were obtained. We evaluated candidate predictive factors of LNM as follows: (1) maximum tumor diameter; (2) macroscopic type; (3) depth of tumor invasion; (4) histological differentiation; (5) infiltrative growth pattern; (6) tumor budding; (7) lymphatic invasion; (8) venous invasion and (9) lympho-vascular invasion (LVI). Both Elastica–Van Gieson staining (EVG) and immunohistochemistry (IHC: D2-40, CD31, CD34) were used to evaluate invasion into the lympho-vascular spaces. For statistical analyses, single and multiple logistic regression were performed. Results. LNM was observed in 37 cases (33.6%). LVI using EVG and IHC was the strongest independent predictor of LNM with an odds ratio of 12.01. Analysis of the relationship between LVI using EVG and IHC and LNM showed a negative predictive value of 94.6%. Conclusions. Evaluation of LVI using EVG and IHC may contribute to predict LNM in sESCC.